Palliative Care: an Interdisciplinary Approach for Patients with Life Threatening Illness - Witjaksono, Maria (Indonesian Journal of Cancer, 2007)
Patients with life threatening illness area characterized by multi-aspect of suffering. These various aspects of suffering area interrelated require a total comprehensive care by an interdisciplinary team. Palliative care means to address the total suffering of the patients and to maintain a rational hope when cure is absurd. Palliative care emphasizes the essential role of the family. Although the awareness about palliative care has been increasing, its development in Indonesia is still left behind compared to that of other Asian Countries. This paper discusses the definition of palliative care, total suffering, interdisciplinary approach, integration of palliative care in cancer management & barriers to Palliative Care.